Modernisasi Pendidikan Islam di Indonesia Awal Abad Ke-XX: Kasus Muhammadiyah - Palahuddin, Palahuddin (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2018)
This paper discusses about the modernization of education conducted by Muhammadiyah at the beginning of the 20th century circa 1911-1932. The modernization was initiated by the founde of Muhammadiyah Kiyai Haji Ahmad Dahlan, indeed effected by religious social conditions of Moslems at that moment which is still lagging behind in all aspects of life. For Muhammadiyah, to solve the problem is modernization of education. Themodernization of education conducted by Muhammadiyah is a way of adapting the educational system of Netherlands in Islamic education. The form of the model of Muhammadiyah school is same as the model of Netherland school. The term of Aziyumardi Azra , referred to as “public school (Netherlands) plus” orStreenbrink referred to as “Ultra Conservative”. In that new and modern school, in addition to religious studies, taught public lessons; the instruments of the study adopted directly as how Netherlands learning. Applied level system and school payment from students. As well as he most phenomenal is the teachers have been given incentives in the form of salary. All of this things, which we now see as something that is good, at that moment it is something very new, strange and even overwhelming.